Peran Announcer Dalam Menyampaikan Informasi Kehilangan Kepada Pasien RS Khusus Mata Sumatera Selatan - Mutiara Zahra (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This article aims to describe the role of announcers in conveying information about lost items to patients and visitors at the Special Eye Hospital in South Sumatra. The study uses a qualitative descriptive method with data collection techniques through participant observation, direct observation, documentation, and the author's active involvement during the internship. Participatory observation was conducted by directly following the announcer's service activities in the hospital environment, so that the author could understand the communication process, information delivery patterns, and obstacles that occurred in the field in depth. The results of the observation indicate that announcers have an important role as a communication medium for hospital services, especially in conveying information about lost items belonging to patients and visitors through a loudspeaker system (public address system). The delivery of information is carried out by paying attention to language clarity, voice intonation, accuracy of information, and communication ethics so that the information can be well received by all message recipients. In its implementation, several obstacles were found such as the busy hospital environment, noise levels, and differences in patient abilities in receiving information. However, announcers try to overcome these obstacles by repeating information, using simple language, and coordinating with related officers to ensure the accuracy of the information conveyed. The presence of announcers has been proven to positively contribute to the effectiveness of service communication and helps create a hospital service environment that is orderly, informative, and responsive to patient needs.